The impacts of fiscal developments on the yield curve - Vránová, Veronika; Maršál, Aleš; Potužák, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
The thesis analyzed the impacts of fiscal developments on the yield curve using quarterly data on the Czech economy over the period 2000:1 -- 2012:4. This thesis thoroughly reviewed the previous theoretical and empirical literature in order to sort out the rather inconclusive results of previous studies according to their main findings and implemented methodology. The empirical part consists of the estimation of the effects of budget deficits and government debt on the spread between the three-month and five-year interest rates, which closely reflects the effects of fiscal policy on the yield curve. The reduced-form equation was estimated by OLS. Since the estimated coefficients were not statistically significantly different from zero, this thesis did not confirm the conventional macroeconomic view of positive impacts on yields.
Vedoucí práce: Aleš Maršál
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses